2018
DOI: 10.4103/sni.sni_344_17
|View full text |Cite
|
Sign up to set email alerts
|

How to perform the wiltse posterolateral spinal approach: Technical note

Abstract: Background:The paraspinal, posterolateral, or Wiltse approach is an old technique that observes the principles of an MIS procedure. The aim of this study was to provide a step-by-step description from the literature of the Wiltse paraspinal approach and analyze its main advantages and limitations.Methods:Here, we provide a step-by-step description of the Wiltse approach. Utilizing PubMed and Lilacs and the Mesh terms “Wiltse approach,” “paraspinal approach,” “muscle sparing approach,” and “lumbar spine,” we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 8 publications
0
23
0
8
Order By: Relevance
“…All standard procedures for correction, including rod de-rotation, compression, distraction, and in-situ bending are to be performed. 7,9 (Fig. 2).…”
Section: Mis With 3 Small Incisionsmentioning
confidence: 97%
See 1 more Smart Citation
“…All standard procedures for correction, including rod de-rotation, compression, distraction, and in-situ bending are to be performed. 7,9 (Fig. 2).…”
Section: Mis With 3 Small Incisionsmentioning
confidence: 97%
“…It approaches the lumbar facet joints through blunt dissection between the medial multifidus and lateral longissimus muscles, providing access to pedicular screws during scoliosis correction, and is considered MIS for AIS surgeries. 7 A retrospective study by Street et al comparing the results of 385 patients done with midline surgical approach and Wiltse approach found that the latter has advantages in reducing the incidence of infection, blood loss, and adjacent segment failure than the midline approach. 8…”
Section: Muscle Sparing or Wiltse Approachmentioning
confidence: 99%
“…Third, bilateral access was provided through an ‐8‐cm‐long midline skin incision. The lumbar dorsal fascia was incised longitudinally at 2.5–3 cm from the posterior midline 12 . The medial multifidus was separated from the lateral longissimus muscle using blunt dissection with fingers.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical procedure for the minimally invasive, Wiltse, posterolateral spinal approach for TLIF has been described in the literature. 4,[15][16][17] The patient was placed prone under general anesthesia. Decompression was performed on the side that was considered the most symptomatic.…”
Section: Surgical Technique For Freehand Fg Mis-tlifmentioning
confidence: 99%